2008
DOI: 10.1007/s00436-007-0852-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the effect of the nematophagous fungi Duddingtonia flagrans, Monacrosporium sinense, and Pochonia chlamydosporia on Ascaris suum eggs

Abstract: The in vitro effect of four isolates of the nematophagous fungi Duddingtonia flagrans (AC 001), Monacrosporium sinense (SF 53), and Pochonia chlamydosporia (VC 1 and VC 4) on eggs of Ascaris suum was evaluated. One hundred thousand A. suum eggs were plated on 2% water-agar with the grown isolates and control without fungus. After 7, 14, and 21 days, 100 eggs were removed and classified according to the following parameters: type 1, lytic effect without morphological damage to eggshell; type 2, lytic effect wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Another approach, which should be investigated further, is the use of egg-predacious microfungi. Several microfungi are used commercially to combat plant-parasitic nematodes in large-scale monocultures, and for example Pochonia chlamydosporia and Paecilomyces lilacinus have also been shown to attack A. suum, Trichuris vulpis, and Toxocara canis eggs in vitro (Araújo et al, 2008;Carvalho et al, 2010;Silva et al, 2010). Hopefully, microfungi can efficiently inactivate large numbers of thick-shelled eggs in stored manure or even on contaminated pastures and thereby help control the parasites in a sustainable way.…”
Section: Inactivation Of a Suum And T Suis Eggsmentioning
confidence: 99%
“…Another approach, which should be investigated further, is the use of egg-predacious microfungi. Several microfungi are used commercially to combat plant-parasitic nematodes in large-scale monocultures, and for example Pochonia chlamydosporia and Paecilomyces lilacinus have also been shown to attack A. suum, Trichuris vulpis, and Toxocara canis eggs in vitro (Araújo et al, 2008;Carvalho et al, 2010;Silva et al, 2010). Hopefully, microfungi can efficiently inactivate large numbers of thick-shelled eggs in stored manure or even on contaminated pastures and thereby help control the parasites in a sustainable way.…”
Section: Inactivation Of a Suum And T Suis Eggsmentioning
confidence: 99%
“…This fungus is widely distributed and has been successfully used in laboratory conditions for the biological control of gastrointestinal nematode parasites eggs of root-knot nematodes (Kerry and Hidalgo 2004), Ascaris suum (Araújo et al 2008), A. lumbricoides (Braga et al 2007) and Taenia taeniaeformis (Braga et al 2008c). The action of this fungus is based on appressorial formation developed from undifferentiated hyphae, which allows the colonization of the egg surface and penetration through both mechanical and enzymatic actions (Lysek and Sterba 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms directly interfere with pasture contamination and animal reinfection, and may help to solve problems with resulting from infection with T. vitulorum and other gastrointestinal parasites (Araújo et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Braga et al (2007) proved that Verticillium chlamydosporium kills eggs of A. lumbricoides. Araújo et al (2008) showed that Pochonia chlamydosporia attacked A. suum eggs. Some nematophagous fungi have been found in regions near archaeological sites in Minas Gerais state, central Brazil (Ribeiro et al, 1999(Ribeiro et al, , 2003 However, few paleoparasitological analyses mentioned the presence of nematophagous fungi.…”
Section: Nematophagous Fungimentioning
confidence: 99%